Greenwashing In Advertising: Decoding Media’s Environmental Claims (International Journal of Environmental Sciences, 2025)
Greenwashing, the practice of making misleading or exaggerated environmental claims, has emerged as a significant challenge in advertising amid growing consumer demand for sustainability. This article explores the multifaceted nature of greenwashing, examining its psychological underpinnings, regulatory frameworks, digital amplification, eco-label complexities, and counter-narratives that empower ethical consumption. Drawing on scholarly literature and real-world examples, including verified cases from India (e.g., Godrej’s mosquito repellent, Zomato’s “Green Delivery”) and hypothetical scenarios, the analysis reveals how cognitive biases, emotional storytelling, and digital platforms enable deceptive claims. Regulatory gaps, particularly in India’s Advertising Standards Council of India (ASCI) and Central Consumer Protection Authority (CCPA) frameworks, allow greenwashing to persist, while unverified eco-labels exacerbate consumer confusion. Counter-narratives through media literacy, advocacy, and technology offer hope for accountability. The article concludes that fostering critical thinking and robust enforcement is essential to align corporate claims with genuine sustainability, contributing to informed consumer choices globally and in India.